Memories of Violence: Micro and Macro History and the Challenges to Peacebuilding in Colombia and Northern Ireland*. Issue 1 (2nd January 2016) - Barkan, Elazar
Abstract: Historical memory of mass violence and war crimes plays a central role in a nation or an ethnic group's cultural identity, but is not given adequate attention in the politics of conflict resolution. The article argues that it is wrong and counterproductive to treat history as exclusively belonging to the past or as too complicated, and therefore to ignore it politically. Northern Ireland invested heavily in various transitional justice and conflict resolution mechanisms, but resolutely avoided efforts to bridge sectarian histories. This experience is juxtaposed to Colombia, where during the peace negotiations a historical commission was established to explore narrowing the sectarian disagreements through legitimizing their historical memories. What can the field of conflict resolution learn from the Colombian experience? Do historical commissions provide an additional tool for transitional justice and conflict resolution?